Development of a Mobile Laboratory for Sudden Onset Disasters. Issue Volume 34:Issue s1(2019) (May 2019) - Marr, Ian; Stephens, Dianne; Baird, Rob; Francis, Josh; Read, David; Coatsworth, Nicholas
Abstract : Introduction: Clinical diagnostics in sudden-onset disasters (SOD) has historically been limited. With poor supply routes, lack of a cold chain, and challenging environmental conditions, many diagnostic platforms are unsuitable. Aim: We set out to design, implement, and evaluate a mobile diagnostic laboratory accompanying a type II emergency medical team (EMT) field hospital. Methods: Available diagnostic platforms were reviewed and selected against infield need. Platforms included HemoCue301/WBC DIFF, i-STAT, BioFire multiplex RT-PCR, Olympus BX53 microscopy, ABO/Rh Grouping, and specific rapid diagnostic tests (RDT). This equipment was trialed in Katherine, Australia and Dili, Timor-Leste. Results: During the initial deployment, validation of FilmArray rt-PCR multiplex tests was successful on blood culture, gastrointestinal, and respiratory panels. HemoCue301 (n = 20) haemoglobin values were compared on Sysmex XN 550 (r = 0.94). Analysis of HemoCue WBC DIFF samples had some variation when compared to Sysmex XN 550, (neutrophils r = 0.88, lymphocytes r = 0.49, monocytes r = 0.16, eosinophils r = 0.70, basophils r = 0.16). i-STAT showed non-significant differences for CHEM4 (n=10), CG8 (n = 10), and TnI (n = 5) against Vitros 250. A further trial of BioFire rt-PCR testing in Dili, Timor-Leste diagnosed 117 causative pathogens on 168 FilmArray test cartridges. Discussion: This mobile laboratory represents a major advance in SOD. Setup of the service was quick (<24hr) and transport to site rapidly. Training was simple and performance consistent. Future deployment in fragmented health systems after sudden onset disasters with EMT2 will now allow broader diagnostics.